Ulnar lengthening in multiple hereditary exostosis with forearm deformity: a long-term follow-up study - Zeng, Bing; Xiao, Han; Yan, An; Liu, Kun; Zhou, Mi; Mei, Haibo (Frontiers in Pediatrics, 2025)
PurposeUlnar lengthening surgery for multiple hereditary exostosis (MHE) with radial head dislocation can achieve satisfactory reduction in the short term. However, its long-term efficacy remains controversial. This study aims to investigate the long-term effects of ulnar lengthening on forearm deformity, functional improvement, and radial head dislocation in pediatric patients.MethodsWe conducted a retrospective study of patients with MHE who underwent ulnar lengthening procedures at Hunan Children's Hospital between 2010 and 2020. The radial articular angle (RAA), ulnar variance (UV), radial variance (RV), and range of motion of the affected forearm and elbow were clinically assessed before surgery and at the last follow-up. The total ulna lengthening distance (LD) and radiographic outcome were also recorded.ResultsThe study included 12 pediatric patients, 6 girls and 6 boys, with a total of 12 forearms affected. The average age was 7.6 ± 2.9 years. The average follow-up time was 63.8 ± 15 months. The mean LD was 2.5 ± 0.7 cm, while the duration of distraction was 141 ± 62.5 days. At the last follow-up, the ulnar length percent, UV, RV, and radial bow (RB) showed statistically significant improvements. The pre-ulnar length percent was 0.91 ± 0.05, while the post-ulnar length percent was 1.0 ± 0.08 (p < 0.001). The pre-UV was −1.1 ± 0.5, while the post-UV was −0.4 ± 0.5 (p < 0.001). The pre-RB was 8.8 ± 1.2, while the post-RB was 7.6 ± 1.4 (p < 0.001). The pre-RV was 0.7 ± 0.6, while the post-RV was 0.4 ± 0.8 (p = 0.02). Postoperative assessment revealed improved forearm supination and elbow pronation mobility to varying extents after the ulnar lengthening procedure. The pre-supination was 56° ± 10.0°, while the post-supination was 67° ± 9.4° (p < 0.001). The pre-pronation was 54° ± 9.3°, while the post-pronation was 65° ± 7.8° (p = 0.003). One pin-track infection was recorded.ConclusionsEarly ulnar lengthening surgery remains a reliable treatment option for patients with MHE who develop severe forearm shortening secondary to ulnar involvement.